LO06: Development of practice recommendations for ED management of syncope by mixed methods. (May 2020) - Thiruganasambandamoorthy, V.; Taljaard, M.; Hudek, N.; Brehaut, J.; Ghaedi, B.; Nguyen, P.; Sivilotti, M.; McRae, A.; Yan, J.; Ohle, R.; Fabian, C.; Le Sage, N.; et al.
Abstract : Introduction: Emergency department (ED) syncope management is extremely variable. We developed practice recommendations based on the validated Canadian Syncope Risk Score (CSRS) and outpatient cardiac monitoring strategy with physician input. Methods: We used a 2-step approach. Step-1: We pooled data from the derivation and validation prospective cohort studies (with adequate sample size) conducted at 11 Canadian sites (Sep 2010 to Apr 2018). Adults with syncope were enrolled excluding those with serious outcome identified during index ED evaluation. 30-day adjudicated serious outcomes were arrhythmic (arrhythmias, unknown cause of death) and non-arrhythmic (MI, structural heart disease, pulmonary embolism, hemorrhage)]. We compared the serious outcome proportion among risk categories using Cochran-Armitage test. Step-2: We conducted semi-structured interviews using observed risk to develop and refine the recommendations. We used purposive sampling of physicians involved in syncope care at 8 sites from Jun-Dec 2019 until theme saturation was reached. Two independent raters coded interviews using an inductive approach to identify themes; discrepancies were resolved by consensus. Results: Of the 8176 patients (mean age 54, 55% female), 293 (3.6%; 95%CI 3.2-4.0%) experienced 30-day serious outcomes; 0.4% deaths, 2.5% arrhythmic, 1.1% non-arrhythmic outcomes. The serious outcome proportion significantly increased from low to high-risk categories (p < 0.001; overall 0.6% to 27.7%; arrhythmic 0.2% to 17.3%; non-arrhythmic 0.4% to 5.9% respectively). C-statistic was 0.88 (95%CI0.86–0.90). Non-arrhythmia risk per day for the first 2 days was 0.5% for medium-risk, 2% for high-risk and very low thereafter. We recruited 31 physicians (14 ED, 7 cardiologists, 10 hospitalists/internists). 80% of physicians agreed that low risk patients can be discharged without specific follow-up with inconsistencies around length of ED observation. For cardiac monitoring of medium and high-risk, 64% indicated that they don't have access; 56% currently admit high-risk patients and an additional 20% agreed to this recommendation. A deeper exploration led to following refinement: discharge without specific follow-up for low-risk, a shared decision approach for medium-risk and short course of hospitalization for high-risk patients. Conclusion: The recommendations were developed (with online calculator) based on in-depth feedback from key stakeholders to improve uptake during implementation.